LAMA MENJALANI HEMODIALISA DENGAN KUALITAS HIDUP PASIEN YANG MENJALANI HEMODIALISA - Mandias, Reagen Jimmy; Gretchen, Michel Aurora (Fakultas Keperawatan, Universitas Klabat, 2025)
The prevalence of chronic kidney disease continues to increase globally, requiring renal replacement therapy such as hemodialysis to sustain life. In the long term, hemodialysis is often accompanied by financial burdens and work limitations, sexual dysfunction, anxiety and depression, and lifestyle changes that reduce the quality of life of patients. The purpose of this study was to determine whether there is a significant relationship between the duration of hemodialysis and the quality of life of patients undergoing hemodialysis at Dr. R. D. Kandou General Hospital in Manado. This study is a quantitative cross-sectional study involving 80 respondents selected using purposive sampling. The instrument used was the Kidney Disease Quality of Life version 1.3, with Cronbach's alpha reliability ranging from 0.580 to 0.999. Data on the duration of hemodialysis was obtained based on the number of years the respondents had undergone therapy. The results of the analysis using Spearman's rho test showed a p-value of 0.101, indicating that there was no significant relationship between the duration of hemodialysis and quality of life in patients at Prof. Dr. R. D. Kandou General Hospital in Manado. In the quality of life domain, dialysis staff support and social support received good ratings. Therefore, it is recommended that families and dialysis staff continue to provide support to improve the motivation and quality of life of hemodialysis patients. Prevalensi penyakit ginjal kronis terus meningkat secara global, dan memerlukan terapi pengganti ginjal seperti hemodialisis untuk mempertahankan hidup. Dalam jangka panjang, hemodialisis kerap disertai beban finansial dan keterbatasan pekerjaan, disfungsi seksual, kecemasan dan depresi, serta perubahan gaya hidup yang menurunkan kualitas hidup pasien. Tujuan penelitan ini untuk mengetahui apakah ada hubungan yang signifikan antara lama menjalani hemodialisa dengan kualitas hidup pasien yang menjalani hemodialisa di RSUP. Dr. R. D. Kandou Manado. Penelitian ini merupakan studi kuantitatif dengan desain cross sectional yang melibatkan 80 responden yang dipilih menggunakan teknik purposive sampling. Instrumen yang digunakan adalah Kidney Disease Quality of Life versi 1.3, dengan reliabilitas cronbach's alpha berkisar 0,580–0,999. Data mengenai lama hemodialisis diperoleh berdasarkan jumlah tahun responden menjalani terapi. Hasil analisis menggunakan uji spearman’s rho menunjukkan p-value 0,101, menandakan tidak terdapat hubungan yang signifikan antara lama menjalani hemodialisis dan kualitas hidup pada pasien di RSUP Prof. Dr. R. D. Kandou Manado. Pada domain kualitas hidup, dukungan staf dialisis dan dukungan sosial memiliki hasil penilaian yang baik. Oleh karena itu, direkomendasikan agar keluarga dan staf dialisis terus memberikan dukungan untuk meningkatkan motivasi dan kualitas hidup pasien hemodialisis.